Vegetation History in Central Croatia from ~10,000 Cal BC to the Beginning of Common Era—Filling the Palaeoecological Gap for the Western Part of South-Eastern Europe (Western Balkans) - Dario Hruševar; Koraljka Bakrač; Slobodan Miko; Nikolina Ilijanić; Martina Šparica Miko; Ozren Hasan; Božena Mitić (Diversity, 2023)
The aim of this study was to reconstruct the vegetation changes, fire history and local landscape dynamics of central Croatia (the western part of south-eastern Europe) from 9800 cal yr BP to the beginning of the Common Era. Pollen, non-pollen palynomorphs and charcoal were analysed for the first time in the aforementioned area by modern palynological methods. Three different assemblage (sub)zones were identified: “Pinus-Fagus-Quercetum mixtum” (Preboreal), “Fagus-Corylus” (Boreal) and “Alnus-Fagus” (Atlantic, Subboreal and older Subatlantic). Additionally, the oldest observation (~9800 cal yr BP) of beech pollen for continental Croatia was confirmed by radiocarbon dating. Our results indicated a possibly milder climate with less extreme temperatures and higher precipitation during the Preboreal chronozone, alongside intensive flooding, a transition from a mosaic of wetland/wet grassland communities to alder carr during the Boreal, and an unusually long multi-thousand-year period, the annual presence of alder on the mire itself. An increase in the number of secondary anthropogenic indicators can be tracked from the 6th century BC to the beginning of the Common Era. Although regional vegetation changes are insufficiently clear, our results fill a gap in the interpretation of vegetation/palaeoenvironmental changes before the Common Era in in this part of Europe.